Dampak Krisis Ekonomi Terhadap Kinerja Industri Susu Segar Dalam Negeri = The Impact of Economic Crisis Toword The Performence of Domestic Dairy Industry - Dewa K.S Swastika; Nyak Ilham; Ikin Sadikin (Agro Ekonomi, 2003)
The Indonesian Dairy Industry wa.s well developed until mid 1997, due to some government protective policies, such as credit far imported dam cattle. and domestic market security. (;orernment determined the Milk Ratio (the ratio between domestic fresh milk and imported milk) that should he satisfied/ by the multinational milk processors (IPS) to run their milk processing lactories. However, the domestic .fresh milk production was not sufficient to meet the raw material far their Jactories. Therefore, in 1996, about 67% of raw materials has w he imported, especially from Australia and New Zealand, At least there were m.o/actors resulting a high import of dairy product. First, the domestic dairy production capacity was limited: second the Indonesian dairy industry was considered as inefficient, so that the price of domesticfresh milk was claimed to be more expensive compared to imported milk. The economic crisis starting from mid 1997, resulting in a high price of imported dairy cattle and feed. On the other hand, this crisis also resulting in a significant increase in price of imported milk. Therefore, the demand for domestic fresh milk by IPS was significantly increased The observations in 6 milk cooperatives (in East and West Java) showed that since economic crisis, all fresh milk offered by all cooperatives to IPS was absorbed. Even IPS provided some incentives (higher price and bonus).* the farmers who have a better quality of milk. There was also price adjustment given by IPS from about Rp. 600 hr in 1996 97 to about Rp. 900 and then about Rp. 1100 ltr in 1998 99. However, the farmers was still complaining. because if they compare milk price to rice price, they recognize that before crisis I liter milk was equivalent to 0.6 kg rice, but after crisis 1 liter milk was equivalent to only 0.4 kg rice. The most important issue that should be anticipated is that "if exchange rate of Rupiah to US Dollar is increased, then imported milk will be cheaper, and IPS will tend to import milk rather than buying domestic fresh milk If this case is happening, it will be a nightmare to farmers who do dairy farm. Therefore, the development and transfer of the more efficient technology in dairy industry should be given a high priority.